A descriptive explanatory study on the challenges to implementing the Communal Land Reform Act to combat illegal fences in communal areas of Namibia : a case study from the Tsumkwe-West Communal Area - Shomeya, Salom Heita (Stellenbosch : Stellenbosch University, 2023)
Thesis (MCom)--Stellenbosch University, 2023.